Inherited Chorioretinal Dystrophies A Textbook and Atlas - Puech, Bernard; De Laey, Jean-Jacques; Holder, Graham E. (Springer Berlin Heidelberg : Imprint: Springer, 2014)
This lavishly illustrated atlas provides indispensable information to clinicians, geneticists and visual scientists working with inherited retinal diseases. It is filled with high-quality images, up-to-date genetic information and comprehensive electrophysiology. The data for each individual disorder have been summarised in an accessible, reader-friendly format for easy reference. The illustrations include colour fundus photographs, fluorescein angiograms, OCT scans, electrophysiological studies and pedigrees. The editors and authors are well-known experts in the field and have drawn upon their extensive experience to produce this unique atlas.